Perilaku Hedonisme Remaja di Mall Panakukkang Makassar - Ritma Resita,; Syamsuddin AB,; Syamsuddin AB, (Jurnal Berita Sosial, 2022)
The social impact caused by the behavior of teenagers in Panakukkang Mall is due to the pattern of adolescent hedonism. The type of research used is qualitative research, with a sociological approach. There are two sources of data in this study, namely, primary data sources and secondary data sources, primary data sources include 10 adolescent informants who tend to behave hedonistically at Panakukkang Mall Makassar. Methods of collecting data by conducting observations, interviews, documentation and library research. The researcher's own research instrument. Data processing and analysis techniques in this study include data reduction, data presentation, and drawing conclusions. The results of this study describe the impact of adolescent hedonistic behavior: 1) Consumptive behavior that buys or uses an item that is not based on rational considerations but only for luxury. 2) Instant mentality brings people not to go through a convoluted process in terms of getting a happiness. The phenomenon of today's youth is the tendency to choose a comfortable, luxurious, and self-sufficient life without working hard. The act of extravagant lifestyle that likes to overuse money. Teenagers feel motivated to behave hedonistically with the following reasons: 1) Wanting to be refreshed because there are lots of college assignments, lots of reports, lots of assignments, basically, he feels that refreshing can make his mind clear again. 2) Recreation, for teenagers, malls are a means of recreation to spend time with their friends by shopping, hanging out at cafes, watching movies.